Nanotribological response of a-C:H coated metallic biomaterials: the cases of stainless steel, titanium, and niobium - Kapnisis, Konstantinos; Constantinou, Marios; Kyrkou, Maria; Nikolaou, Petros; Anayiotos, Andreas; Constantinides, Georgios (My University, 2018)
Background Wear and corrosion have been identified as two of the major forms of medical implant failures. This study aims to improve the surface, protective and tribological characteristics of bare metals used for medical implants, so as to improve scratch resistance and increase lifetime. Methods Hydrogenated amorphous carbon (a-C:H) films were deposited, using plasma enhanced chemical vapor deposition (PECVD), on stainless steel (SS), titanium (Ti) and niobium (Nb) metal plates. Nanomechanical and nanotribological responses were investigated before and after a-C:H deposition. Film thickness and density were quantified through X-ray reflectivity, and surface morphology before and after deposition were measured using atomic force microscopy, whereas the tribomechanical characteristics were probed using instrumented indentation. Results and conclusions Films of approximately 40 nm in thickness and density of 1.7 g/cm3 were deposited. The a-C:H films reduce the roughness and coefficient of friction while improving the tribomechanical response compared with bare metals for Ti, SS and Nb plates. The very good tribomechanical properties of a-C:H make it a promising candidate material for protective coating on metallic implants.
Keywords: Biomaterials; Hydrogenated amorphous carbon film; Nanoscratch; Nanotribology